Gas production of napier grass and corn stover inin vitro rumen fermentation - Mohd Yahya, Muezzudin (2015)
In Malaysia, sweet corn is one of the popular crops. The corn stover not being fully utilized by farmers. Napier grass has been used widely in Malaysia as livestock feeding. A study was undertaken to compare the Napier grass (Pennisetum purpureum) and corn stover (F1 Sweet Corn- Sh2) and their parts of plant for dry matter (DM), ash, crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL), and in vitro digestibility. 9 samples were collected randomly for each Napier grass and corn stover. Each plant were divided into three sampling parts which are leaf part (n=3), stem part (n=3) and whole plant (n=3). Corn stover sample was collected after the corn grain was harvested. The DM and ash of corn stover was higher (P<0.05) than Napier grass, while the content of CP, NDF and ADF was higher (P<0.05) in Napier grass compare to corn stover. Higher ADL reading was shown by, the corn stover. The DM, ash and CP content was higher (P<0.05) in Napier leaf compare to other parts of Napier grass, while the Napier stem have higher (P<0.05) in NDF, ADF and ADL contain., the DM, ash and CP content in corn leaf was higher (P<0.05) compared to the corn stem that have higher (P<0.05) NDF, ADF and ADL contain, vice versa. From gas production analysis, corn stover showed higher digestibility (P<0.05) than Napier grass. Between Napier grass and corn stover, the leaf part showed higher digestibility (P<0.05) compare to other parts. Eventhough the corn stover was an agriculture by-product, it showed higher digestibility (P<0.05) compared to Napier grass that was meant only for animal feed. For the recommendation, the corn stover (agriculture by-product) can be used for livestock feeding with the great nutrient content compare to the Napier grass. Farmers need to mix well the fodder because the nutrient content in different part of plant is varies.